Dynamic Capability Drives Digital Transformation: SEM Evidence onSustained Competitive Advantage in Emerging Markets - Supriyadi; Firmansyah (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2026)
This study aims to examine the influence of dynamic capabilities on sustained competitive advantage and to investigate the mediating role of digital transformation in firms in emerging markets. Based on Dynamic Capabilities Theory, digital transformation is conceptualized as a process driven by strategic capabilities, rather than simply technology adoption. Data were collected from 247 top- and middlelevel managers from medium- and large-sized firms in Indonesia. Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed relationships. The results show that dynamic capabilities have a significant positive influence on digital transformation ( = 0.61, p ¡ 0.001) and sustained competitive advantage ( = 0.29, p ¡ 0.01). Furthermore, digital transformation significantly enhances sustained competitive advantage ( = 0.54, p ¡ 0.001). Mediation analysisconfirmed that digital transformation partially mediates the relationship between dynamic capabilities and sustained competitive advantage (indirect = 0.33, p ¡ 0.001), indicating that digital transformation acts as a strategic transmission mechanism. This model explains 37% of the variance in digital transformation and 58% of the variance in sustained competitive advantage. In conclusion, this study shows that dynamic capabilities are important drivers of sustained competitive advantage, both directly and indirectly through digital transformation. These findings highlight the importance of aligning digital initiatives with organizational capabilities to achieve long-term competitive performance in a dynamic and uncertain environment.